Market Discipline and Banking Crises in Russia: A Reverse Engineered Pitch - Nurhastuty Wardhani (Journal of Accounting and Management Information Systems (JAMIS), 2018)
Research is a long journey for a new early career researcher and PhD student. At the early stage, the new researcher needs to build up the "brick" foundation and to communicate well with the advisory team regarding their research progress. Pitching research developed by Faff (2015; 2017) can be a strong tool for answering the confusion of beginner researcher in their initial journey. This pitching research letter offers the author's experience in implementing Faff's (2015; 2017) template to the reverse engineering pitch in the area of banking market discipline. This pitching research template has been applied to a published article by Karas et al. (2013), who investigated the market discipline in Russian banking. In addition, this letter conveys a personal reflection regarding the pitching template.
Keywords: M2; M1; E43; G01; 650; Pitching Research Letter; Reverse Engineering Pitch; Market discipline; Banking crisis; Russia